Role of Lactic Acid as Predictor of Mortality in Patients with Acute Myocardial Infarction - Novi Khila Firani; Theresa Sugiarti Oetji (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
The hypoxic-ischemic condition causes tissue metabolic abnormalities and organ dysfunction, characterized byelevated blood lactic acid levels. It is suspected that increased lactic acid in Acute Myocardial Infarction (AMI) patients couldincrease mortality risk. This study aimed to determine whether increased lactic acid levels could be used as a predictor ofmortality in AMI patients. The analytical observational-cohort study was performed on AMI patients who were admitted toDr. Saiful Anwar Malang Hospital from January 2018 to December 2019. Research subjects were divided into two groups, thegroup of deceased and living AMI patients, who were tested for lactic acid, troponin-I, CKMB, and creatinine levels atadmission. Diabetes mellitus and septic patients were excluded. For analysis of lactic acid as a predictor of mortality, ROCcurve analysis and odds ratio were used. There found that lactic acid levels in the deceased AMI patients group were highercompared to that of the living AMI patients (p < 0.05). The sensitivity and specificity values of lactic acid as a predictor ofmortality in AMI patients at a cut-off of 3.5 mmol/L were 66.7% and 80%, respectively. Odds ratio analysis showed that AMIpatients with lactic acid levels more than 3.5 mmol/L had 8 times greater mortality risk than those whose level less than 3.5mmol/L. It was concluded that lactic acid level can be used as an indicator to predict the mortality of AMI patients.